MEASURING PERFORMANCE AMONG COMMUNITY MIDWIVES IN LOW-RESOURCE SETTINGS: A MIXED-METHODS STUDY IN SUDAN - Abu-Agla, Ayat Siddig (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2021)
Sudan faces remarkable health workforce challenges including shortages and skewed geographical distribution. The complexity of the health workforce landscape, the country’s volatile geopolitical climate, and an unfavorable health labor market marked by weak absorption capacity and poor retention policies, led to significant migration of the country’s health workforce involving nearly 60% of the physician workforce. Sudan’s response to the health workforce crisis included the introduction of a primary health care (PHC) expansion programme in 2013, which had amongst its priorities to increase human resources for reproductive, maternal, and child health and improve the performance of Sudan’s health workforce. To achieve this, the Sudan Federal Ministry of Health (FMoH) trained and deployed three new frontline health workers: the community midwife (CMW), the community health worker (CHW), and the medical assistant. Despite the performance of the health workforce being prioritised and noted as important by the Sudan’s National Health Sector Strategy, the literature on how to optimise health provider performance within Sudan remains scarce. To date, no performance measure has been established at the Federal or State levels of the health sector. Performance measurement is particularly problematic for health managers, who have no systematic way to monitor the progress of the CMWs under their supervision. Indeed, how to best measure performance in developing countries, such as Sudan, remains a highly debated topic in the literature. Specifically, there remain significant gaps in how performance is conceptualised. The current knowledge gaps around what factors makeup performance and what determines performance represent critical issues in performance measurement. Therefore, the goal of the current research was to develop a practical measure of the performance of CMWs in Sudan.In light of the challenges mentioned above and the recognised role of performance as a priority area to strengthen human resources for health(HRH) in Sudan, this thesis first reviews the current landscape of HRH, its challenges, and identifies current gaps in performance knowledge, policy, and practice, as well as presents current debates within performance measurement, theories, and frameworks. This is followed by an in-depth contextual description of national Reproductive, Maternal, and Child health (RMCH) trends over time, set against the recent geopolitical climate, and a review of relevant RMCH research, policies, strategies, and programmes in Sudan. The current study then adopts an implementation research approach using mixed-methods across three distinct research phases: an exploratory phase, a tool development phase, andthe tool testing phase. As part of the exploratory phase, the firstresearch objective was to determine what factor(s) constitute ‘performance’ of maternal health workers in low and middle-income countries. This was achieved through a systematic review ofthe performance literature, focusing on maternal health care providers in low and middle-income countries (LMICs). Results of the systematic review identified sixteen key constructs, used to measure RMCH cadre performance across LMICs. The majority of studies (n = 26) measured the quality of care (n = 24) as a principal measure of performance. Health worker knowledge (n = 17), skills (n = 10), competency (n = 7), job satisfaction (n = 7), compliance (n = 3) and motivation (n = 4), also featured among the most commonly measured components of performance. Results highlight inconsistencies within the literature as to whether these constructs are best conceptualised as direct observations of performance or as determinants of performance. The second objective was to determine what factor(s) constitute ‘performance’ of communitymidwives in Sudan. A series of key informant interviews (KIIs), focus group discussions, and participatory workshops were conducted with key stakeholders. This resulted in the identification of availability, accessibility, and acceptability as essential prerequisites for the measure of performance of CMWs in Sudan. Determinants of performance identified were categorised as either contextual, from both the supply or demand side of the health system, or individual/motivational factors. Demand side contextual determinants potentially influencing the performance of the CMW included socio-cultural health beliefs, diet norms, access to clean water, taboos around family planning, financial hardship, choice of healthcare, and having previously experienced mistreatment from a health worker. Key informants further identified the remuneration, quality of training of the CMWs, work environment, including access to health facilities, and availability of consumables, as performance determinants. Individual/motivational factors, on the other hand, included seven components that reflected the motivation of CMWs to choose this profession. These include pride, appreciation, funding opportunity, and happiness in helping others, saving lives, and combating harmful traditional practices.The results were synthesised with the results of the systematic literature review to propose a theoretical framework for the measure of CMW performance in Sudan, depicting both the determinants and components of performance for CMWs in the contextof Sudan. The identified performance of CMWs in Sudan consists of three primary constructs: knowledge, competency, compliance, as determined by job satisfaction, supervision, and motivation. During the tool development phase, and aligned with implementation research, participatory approaches with key stakeholders, including reproductive health state coordinators, policy makers, community midwives, and beneficiaries, were again used to develop contextually relevant items for each of the constructs represented by the theoretical framework derived during the exploratory phase. The results of this phase yielded an initial version of a tool to measure performance among community midwives in Sudan. In specific, the tool was developed to measure aspects of CMW Knowledge (13-items), Compliance (11-items), Competency (6-items), as indicators of performance, as well as Job Satisfaction (15-items), Supervision (5-items), and Motivation (11-items), as determinants of performance. The resulting tool was subsequently taken forward for testing in the final phase of the thesis: The tool testing phase. The fourth objective of assessing the validity of the performance measurement tool was realised through applying measurement modelling procedures. Responses gathered using the CMW performance measurement tool underwent latent variable modeling procedures, namely, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to determine the factorstructure of the performance measure. Results supported a three-factor structure of performance, characterised by ‘Know-How,’ ‘Know-what,’ and ‘Will-To’ factors. A revised theoretical framework describing the determinants and components of performance of community midwives in Sudan is presented.This study contributes to existing knowledge by developing a contextually relevant tool to measure community midwives’ performance in Sudan. In the short term, it is expected that the results of this study will be used to inform national policy, management and training programmes, while also contributing to the growing literature in the area of health worker performance by identifying and measuring the performance of frontline maternal health workers in similar low-resource settings. New knowledge derived from this thesis is of particular relevance to NGOs, governments, policymakers, and health programme implementers focused on health worker performance improvement. In the long-term, it is expected that the results of this study will contribute to better performance monitoring and better human resource management, both nationally and internationally.
APPROVED
Keywords: HEALTH WORKFORCE; LOW-RESOURCE SETTING; LMICs; PERFORMANCE MEASUREMENT TOOL; HEALTH WORKER; INDUSTRIAL/ORGANISATIONAL PSYCHOLOGY; COMMUNITY MIDWIVES; HUMAN RESOURCES FOR HEALTH; PERFORMANCE; UNIVERSAL HEALTH COVERAGE; DISRUPTED HEALTH SYSTEM; IMPLEMENTATION RESEARCH; HEALTH SYSTEM RESEARCH; SYSTEM THINKING; MIXED-METHOD STUDY; SUDAN